2011
DOI: 10.1002/dvdy.22774
|View full text |Cite
|
Sign up to set email alerts
|

Induction of canonical Wnt signaling by alsterpaullone is sufficient for oral tissue fate during regeneration and embryogenesis in Nematostella vectensis

Abstract: Although regeneration is widespread among metazoa, the molecular mechanisms have been studied in only a handful of taxa. Of these taxa, fewer still are amenable to studies of embryogenesis. Our understanding of the evolution of regeneration, and its relation to embryogenesis, therefore remains limited. Using β-catenin as a marker, we investigated the role of canonical Wnt signaling during both regeneration and embryogenesis in the cnidarian Nematostella vectensis. The canonical Wnt signaling pathway is known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 29 publications
5
48
0
Order By: Relevance
“…Furthermore, in Hydra, activation of canonical Wnt signaling is sufficient to cause tentacle outgrowth along the body column (Hassel et al, 1993;Broun et al, 2005). By contrast, recent studies in Nematostella show that ectopic activation of canonical Wnt signaling can only induce tentacle and oral fates at the aboral pole of developing animals, not along the body column (Trevino et al, 2011). Additionally, we have demonstrated that Notch signaling is required for tentacle elongation in Nematostella (Fig.…”
mentioning
confidence: 52%
“…Furthermore, in Hydra, activation of canonical Wnt signaling is sufficient to cause tentacle outgrowth along the body column (Hassel et al, 1993;Broun et al, 2005). By contrast, recent studies in Nematostella show that ectopic activation of canonical Wnt signaling can only induce tentacle and oral fates at the aboral pole of developing animals, not along the body column (Trevino et al, 2011). Additionally, we have demonstrated that Notch signaling is required for tentacle elongation in Nematostella (Fig.…”
mentioning
confidence: 52%
“…[16][17][18][19] A large number of studies have suggested that WNT signaling is aberrantly activated in GBM and that it promotes GBM growth and invasion via the maintenance of stem cell properties. [20][21][22][23] Here, we will review recent studies from the literature that have described the functions of WNT/β-catenin signaling in development and cancer, with particular emphasis on [24][25][26][27][28][29] genetic and epigenetic alterations that lead to aberrant WNT pathway activation in GBM. We will then discuss the development of therapeutic approaches based on the inhibition of WNT activation and the current status of clinical trials based on agents targeting the WNT pathway.…”
mentioning
confidence: 99%
“…Nematostella GSK3-β contained the conserved phosphorylation sites known in Bilateria [6, 50] and its inhibitor alsterpaullone (ALP) is commonly used in Cnidaria, including in Nematostella [32, 33]. Using ALP in the presence of Hg caused a reduction in fos1 and jun1 transcript levels after 1h, suggesting that GSK3-β is an activator of AP-1 transcription in Nematostella (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Anemones were exposed to HgCl 2 at a concentration of 200 µg/L (0.74 µM) in 10 ml medium for 1, 6 and 24 h and compared to control untreated anemones. The kinase inhibitors were reported to display high sequence specificity and are widely used in different organisms including, to some extent, in Nematostella [26, 30-33]; however, their specificity in Nematostella has not yet been established. Kinase inhibitors dissolved in DMSO or only DMSO (control) were added two hours before the introduction of Hg.…”
Section: Methodsmentioning
confidence: 99%